Unveiling the potential of fine arts education in enhancing resilience among Chinese gifted students - Dong, Zhe; Zhang, Ying (Frontiers in Psychology, 2024)
The present study aims to investigate the intricate dynamics shaping the resilience of Chinese gifted students, while considering the interplay between fine arts education (FAE), creativity and self-efficacy (SE). By focusing on the transformative potential of FAE, this study accentuates the mediating role of creativity and SE of Chinese gifted students. A structured set of questions is administered to gifted young adults with a recovery rate of 93.21%. Then, this study adapts the Maus scale (1938) to measure FAE, Connor-Davidson Resilience scale to measure resiliency, along with the Kaufman scale and Schwarzer and Jerusalem scale to respectively compute the creativity and SE of gifted Chinese students. This study performs a number of statistical tests, including the correlation matrix, ANOVA, confirmatory latent factor model test, while exploring the mediating effects for resiliency and creativity, by employing the SPSS Statistics 29.0, bootstrap, and AMOS 25.0 software. Current results demonstrate the critical role of FAE in enhancing emotional resilience, creativity, and SE among gifted students. This study pleads to integrate FAE into curricula to better address the intellectual and emotional challenges of gifted young adults, thereby developing some essential coping skills for their emotional well-being. Besides, this study shows the importance of art therapy and global initiatives for enhancing resilience and thus prepare the gifted young adults for future challenges.